Flexible multi-walled carbon nanotubes/polyvinylidene fluoride membranous composites with weakly negative permittivity and low frequency dispersion. (May 2022) - Sun, Kai; Duan, Wenxin; Lei, Yanhua; Wang, Zongxiang; Tian, Jiahong; Yang, Pengtao; He, Qifa; Chen, Min; Wu, Haikun; Zhang, Zheng; Fan, Runhua
Graphical abstract: MWCNTs/PVDF membranous composites with a weakly negative permittivity and low frequency dispersion presented an excellent flexibility, and the absolute value of negative permittivity can be as low as approximately 10 in the whole test frequency range. Abstract: Flexible composites with negative permittivity have great potentials in flexible electronics and wearable devices. To improve their working performance, it is critical to search for such materials that possess weakly and stable negative permittivity in a wide frequency range. In this work, the polyvinylidene fluoride (PVDF) was selected as the flexible matrix and the modified multi-walled carbon nanotubes (MWCNTs) were used as functional fillers to prepare MWCNTs/PVDF membranous composites with a weakly negative permittivity. When the content of MWCNTs exceeded 13 wt%, the negative permittivity conforming to Drude model appeared. The absolute value of negative permittivity can be as low as approximately 10 in the whole test frequency range, presenting a low frequency dispersive behavior. It demonstrated that the weakly negative permittivity was ascribed to the dilution of electrons in the resulting composites, and the high electron mobility in MWCNTs was responsible for the low frequency dispersion. The MWCNTs/PVDF membranous metacomposites with a twisted and foldable flexibility can contribute to the development of flexible metamaterials and enrich their significant applications.